Survival and Side Effects of Cisplatin/Cyclophosphamide and Carboplatin/Paclitaxel Adjuvant Chemotherapy in Stage IC-IV Ovarian Cancer - Markus, Unedo H; Winarto, Hariyono; Andrijono, Andrijono; Sutrisna, Bambang (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To compare the survival and side effects in epithelial ovarian cancer patients receiving adjuvant chemotherapy of cisplatin/ cyclophosphamide and carboplatin/paclitaxel. Method: We recruited epithelial ovarian cancer patients receiving cisplatin/cyclophosphamide (group A) or carboplatin/paclitaxel (group B) adjuvant chemotherapy after surgery. Chemotherapy was given for six cycles. Overall survival and side effects were assessed. Result: A total of 49 patients were recruited, consisting of 25 patients for group A and 24 patients for group B. In this study, the overall survival of stage IC-IV ovarian cancer patients was 37.3 months in group A (95%CI=31.86-43.46) and 35.5 months (95%CI= 13.93- 43.46) in group B (p